Phosphorus stably bonded to a silica gel matrix through niobium bridges. Issue 31 (21st August 2015) - Clayden, N. J.; Accardo, G.; Mazzei, P.; Piccolo, A.; Pernice, P.; Vergara, A.; Ferone, C.; Aronne, A.
<x xml:space="preserve">Abstract</x> Amorphous niobium–phosphorus–silicon mixed oxide gels in which phosphorus remains stably bonded to a siloxane matrix by niobium bridges have been obtained by a new hydrolytic sol–gel route.